PID Control for Temperature and Motor Speed Based on PLC - Al Andzar, Muhammad Faqihuddin; Puriyanto, Riky Dwi (Association for Scientic Computing and Electronics, Engineering (ASCEE), 2019)
Transesterification process of used cooking oil to biodiesel need heating and mixing of ingredients and catalyst at temperature of 30-65oC and stirring speed of 700 rpm for 60 minutes. This research builds a prototype of biodiesel reactor control system to control those process automatically. The system is built using heater element, LM35DZ temperature sensor, DC motor to drive the stirrer, and rotary encoder sensor. PLC OMRON CP1E NA20DR-A is used as system controller by using PID algorithm. The results of this research shows that this system works well as expected. Test results of motor speed control shows, at 700 rpm set point this system gives stable response at 100 % Proportional band, 1,6 s Integral, and 0,2 derivative PID parameters, the system at this setting gives fast rise time and have small overshoot. Test result of temperature control shows, at 60oC set point this system works well at 1% proportional band, 400 s integral, and 0 s derivative PID parameters, the system at this setting gives fast rise time and stable steady state.